An electrochemical device and a vehicle

CN122950644APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511287499.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而负极活性材料,尤其是硅基材料在嵌锂时会产生较大的体积膨胀,导致负极活性物质从集流体上脱落,影响电池的循环稳定性

Benefits of technology

[0019]本申请中,当电极组件中的负极活性材料在充放电过程中发生体积膨胀时,会使负极活性材料从集流体上脱落。如果在充放电过程中对负极极片施加一定的压强,可以抵消部分由负极活性材料膨胀产生的应力,从而降低负极极片的膨胀程度。因此,本申请在充放电过程中控制负极极片所在环境的压强P与n种负极活性材料的平均膨胀系数满足:由此使得对负极极片施加的压强P可以抑制负极活性材料产生的体积膨胀,从而减少负极活性材料脱落的概率,并且降低由于负极活性材料的脱落对SEI膜的破坏,进而提高电化学装置的首次库伦效率、容量和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005589265200000041
    Figure BDA0005589265200000041
  • Figure BDA0005589265200000121
    Figure BDA0005589265200000121
  • Figure BDA0005589265200000131
    Figure BDA0005589265200000131
Patent Text Reader

Abstract

This application relates to an electrochemical device. The electrochemical device includes an electrode assembly, which includes a negative electrode sheet. The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. The negative electrode film layer includes an assembly of negative electrode active materials, which includes n types of negative electrode active materials, where n ≥ 1. The average coefficient of thermal expansion of the n types of negative electrode active materials satisfies the following relationship with the pressure P of the environment in which the negative electrode sheet is located: where x i α represents the mass fraction of the i-th negative electrode active material among n types of negative electrode active materials, based on the total mass of the negative electrode active material assembly. i Let ρ be the volume expansion rate of the i-th negative electrode active material. i Let be the density of the i-th negative electrode active material. This electrochemical device exhibits improved capacity, initial coulombic efficiency, and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical technology, specifically relating to an electrochemical device and a vehicle. Background Technology

[0002] Due to the scarcity of fossil energy and the environmental impact of fossil fuel combustion, the demand for green and clean energy and corresponding energy storage technologies has surged, driving the development of rechargeable batteries. Electrochemical devices, with their advantages of high specific energy, long lifespan, and no memory effect, have been widely used in energy storage systems, electric vehicles, and portable electronic devices.

[0003] In the performance development of electrochemical devices, to improve energy density, negative electrode active materials (such as silicon-based materials) with high specific capacity are typically added to the negative electrode. However, negative electrode active materials, especially silicon-based materials, undergo significant volume expansion during lithium intercalation, causing the negative electrode active material to detach from the current collector, affecting the battery's cycle stability. Furthermore, the repeated formation of the solid electrolyte interphase (SEI) film continuously consumes lithium ions, leading to a decrease in ionic and electronic conductivity, as well as the loss of negative electrode active material. This results in a reduction in the battery's initial coulombic efficiency and a continuous decline in battery capacity.

[0004] Therefore, improving the capacity, initial coulombic efficiency, and cycle performance of electrochemical devices has become an urgent technical problem to be solved. Summary of the Invention

[0005] In view of this, the main objective of the present invention is to provide an electrochemical device and vehicle. This electrochemical device has improved capacity, initial coulombic efficiency, and cycle performance.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0007] A first aspect of the present invention provides an electrochemical device comprising an electrode assembly, the electrode assembly including a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a set of negative electrode active materials, the set of negative electrode active materials including n kinds of negative electrode active materials, n≥1; the average coefficient of thermal expansion of the n kinds of negative electrode active materials. The pressure P of the environment where the negative electrode is located satisfies: in, x i α represents the mass fraction of the i-th negative electrode active material among n types of negative electrode active materials, based on the total mass of the negative electrode active material assembly. i Let ρ be the volume expansion rate of the i-th negative electrode active material. iLet be the density of the i-th negative electrode active material.

[0008] In some implementations, the pressure P is 0 MPa-300 MPa.

[0009] In some implementations, the negative electrode active material includes carbon-based materials, silicon-based materials, or lithium titanate.

[0010] In some embodiments, the negative electrode active material set includes carbon-based materials and silicon-based materials, or the negative electrode active material set includes lithium titanate.

[0011] In some embodiments, the carbon-based material includes one or more of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, and hard carbon.

[0012] In some embodiments, the silicon-based material includes one or more of elemental silicon, silicon oxides, and silicon-carbon composites.

[0013] In some implementations, the electrolyte includes a solid electrolyte material.

[0014] In some embodiments, the solid electrolyte material includes one or more of oxide solid electrolyte materials, sulfide solid electrolyte materials, halide solid electrolyte materials, nitride solid electrolyte materials, and hydride solid electrolyte materials.

[0015] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes at least one of a lithium phosphate with an olivine structure, a lithium transition metal oxide, and a modified compound thereof.

[0016] In some implementations, the electrode assembly includes a wound electrode assembly.

[0017] In some embodiments, the electrochemical device also includes a pressurizing device for providing pressure P to the negative electrode.

[0018] A second aspect of the invention provides a vehicle that includes the electrochemical device of the first aspect.

[0019] In this application, when the negative electrode active material in the electrode assembly expands in volume during charging and discharging, it may detach from the current collector. Applying a certain pressure to the negative electrode sheet during charging and discharging can partially offset the stress generated by the expansion of the negative electrode active material, thereby reducing the degree of expansion of the negative electrode sheet. Therefore, this application controls the pressure P of the environment surrounding the negative electrode sheet and the average expansion coefficient of the n negative electrode active materials during charging and discharging. satisfy: This allows the pressure P applied to the negative electrode to suppress the volume expansion of the negative electrode active material, thereby reducing the probability of the negative electrode active material falling off and reducing the damage to the SEI film caused by the falling off of the negative electrode active material, thus improving the initial coulombic efficiency, capacity and cycle performance of the electrochemical device. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0021] Unless otherwise specified, the terms "comprising" and "including" as used in this invention can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.

[0022] Unless otherwise specified, the term "or" is inclusive in this invention. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0023] Unless otherwise specified, in this invention, "one or more" or "at least one" refers to any one, any two, or any two or more of the listed items. "Several" refers to any two or more.

[0024] The first aspect of this application provides an electrochemical device. This electrochemical device is a battery module or battery pack, but the embodiments of this application are not limited to this.

[0025] In this application, "battery module" refers to a device formed by combining multiple power battery cells (electrode components) in series or parallel, and equipping them with components such as a pressurizing device, a management system, and a thermal management system. The pressurizing device, as an important component of the battery module, applies appropriate pressure to the battery cells during charging and discharging to ensure electrode stability and guarantee battery performance and lifespan.

[0026] In this application, "battery pack" refers to a device formed by the further integration of multiple battery modules, plus a casing, high-voltage system, low-voltage system, and other auxiliary components. This may also include a pressurization device, and its overall goal is to provide a stable power source for vehicles and other equipment.

[0027] In this application, the electrochemical device includes an electrode assembly, which comprises a positive electrode, a negative electrode, a separator, and an electrolyte. During the charging and discharging process of the electrochemical device, active ions repeatedly insert and extract between the positive and negative electrode. The electrolyte acts as a conductor between the positive and negative electrode. The separator is positioned between the positive and negative electrode, primarily to prevent short circuits between them while allowing ions to pass through.

[0028] This application provides an electrochemical device comprising an electrode assembly, the electrode assembly including a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a set of negative electrode active materials, the set of negative electrode active materials including n kinds of negative electrode active materials, n≥1; the average coefficient of thermal expansion of the n kinds of negative electrode active materials. The pressure P of the environment where the negative electrode is located satisfies: in, x i α represents the mass fraction of the i-th negative electrode active material among n types of negative electrode active materials, based on the total mass of the negative electrode active material assembly. i Let ρ be the volume expansion rate of the i-th negative electrode active material. i Let be the density of the i-th negative electrode active material.

[0029] In this application, when the negative electrode active material in the electrode assembly expands in volume during charging and discharging, it may detach from the current collector. Applying a certain pressure to the negative electrode sheet during charging and discharging can partially offset the stress generated by the expansion of the negative electrode active material, thereby reducing the degree of expansion of the negative electrode sheet. Therefore, this application controls the pressure P of the environment surrounding the negative electrode sheet and the average expansion coefficient of the n negative electrode active materials during charging and discharging. satisfy: This allows the pressure P applied to the negative electrode to suppress the volume expansion of the negative electrode active material, thereby reducing the probability of the negative electrode active material falling off and reducing the damage to the SEI film caused by the falling off of the negative electrode active material, thus improving the initial coulombic efficiency, capacity and cycle performance of the electrochemical device.

[0030] In this application, the volume expansion rate α of the i-th negative electrode active material iThe determination can be performed using instruments and methods known in the art. For example, a scanning electron microscope or a high-resolution optical microscope can be used. As an example, the test method can be as follows: Before charging, the negative electrode sheet is polished using a cross-section polisher (e.g., the IB-09010CP argon ion cross-section polisher from JEOL Corporation). After polishing, the cross-section of the negative electrode sheet before charging is tested using a scanning electron microscope: multiple (e.g., 20) different regions are randomly selected in the cross-section of the negative electrode sheet for scanning and testing. At a certain magnification (e.g., 1000x), the particle size of all negative electrode active material particles in each test region is counted, which is the particle size of the negative electrode active material particles in that region. The average value of the test results of multiple test regions is taken as the particle size d1 of the negative electrode active material particles before charging. After charging the electrochemical device to 4.25V with a current of 0.33C, the electrochemical device is disassembled, and the negative electrode sheet after charging is polished using the above method, and the particle size d2 of the negative electrode active material particles after charging is measured. Comparing the particle size of the negative electrode active material before and after charging, according to the formula: α i =(d1 / d2) 3 The volume expansion rate of the i-th negative electrode active material was calculated.

[0031] In this application, the types of negative electrode active materials contained in the negative electrode sheet, as well as the mass percentage of each type of negative electrode active material, can be tested using inductively coupled plasma mass spectrometry (ICP-MS) or inductively coupled plasma optical emission spectroscopy (ICP-OES). Once the types of negative electrode active materials are determined, their density can be determined.

[0032] In this application, the average expansion coefficient of n kinds of negative electrode active materials It is calculated using the following formula:

[0033]

[0034] When n=1, that is, when the negative electrode active material includes only one type of material, the average coefficient of thermal expansion of n types of negative electrode active materials is... Where α is the volume expansion rate of the negative electrode active material, p is the density of the negative electrode active material, and α and ρ are calculated by the above test method.

[0035] When n≥2, the average coefficient of thermal expansion of n kinds of negative electrode active materials Where, α i and ρ i The above test method was used to calculate the result.

[0036] In some embodiments, the pressure P is between 0 MPa and 300 MPa. A pressure P within this range is beneficial for reducing safety issues caused by excessive internal pressure in the electrochemical device, thereby further extending the lifespan of the electrochemical device. Exemplarily, the pressure P is any value within the range of 0 MPa, 20 MPa, 50 MPa, 80 MPa, 100 MPa, 150 MPa, 200 MPa, 250 MPa, 300 MPa, or any combination thereof.

[0037] The following is a further explanation of the components of the electrochemical device:

[0038] Negative electrode sheet

[0039] In this application, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0040] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0041] In some embodiments, the negative electrode active material includes carbon-based materials, silicon-based materials, or lithium titanate. Carbon-based materials have good conductivity and structural stability, silicon-based materials have high specific capacity, and lithium titanate has high structural stability and safety. By adding the above-mentioned types of negative electrode active materials, it is beneficial to improve the initial coulombic efficiency, cycle performance, and capacity of the electrochemical device.

[0042] In some embodiments, the negative electrode active material assembly includes carbon-based and silicon-based materials. Silicon-based materials possess extremely high theoretical specific capacity; by selecting silicon-based materials, the capacity and energy density of the electrochemical device can be significantly increased. Carbon-based materials, on the other hand, exhibit better flexibility and stability, and can act as a buffer layer to effectively mitigate volume changes in silicon-based materials, reduce electrode structure damage, and improve the cycle stability of the electrochemical device. Therefore, the combined use of carbon-based and silicon-based materials can enhance the energy density and cycle performance of the electrochemical device.

[0043] In some embodiments, the negative electrode active material set includes lithium titanate. Lithium titanate has fast charge-discharge capability, long cycle life and high safety, and a low volume change rate during cycling. Therefore, using lithium titanate as the negative electrode active material can improve the initial coulombic efficiency, fast charge performance and cycle performance of the electrochemical device.

[0044] In some embodiments, the carbon-based material includes one or more of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, and hard carbon. Carbon-based materials have good electrical conductivity and structural stability. By adding the above-mentioned types of carbon-based materials, it is beneficial to provide conductive channels in the negative electrode, reduce the internal resistance of the electrochemical device, and improve the cycle life of the electrochemical device.

[0045] In some embodiments, the silicon-based material includes one or more of elemental silicon, silicon oxides, and silicon-carbon composites. Silicon-based materials have high specific capacity, and the addition of the aforementioned types of silicon-based materials is beneficial for improving the capacity and energy density of electrochemical devices.

[0046] In some embodiments, the volumetric particle size distribution (Dv50) of the negative electrode active material is from 5 μm to 15 μm. A volumetric particle size distribution (Dv50) within this range provides the negative electrode active material with a suitable specific surface area, which is beneficial for efficient ion transport, reduces polarization, and thus improves the charge / discharge rate performance of the electrochemical device. Exemplarily, the volumetric particle size distribution (Dv50) of the negative electrode active material is any value within the range of 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or any combination thereof.

[0047] In this application, the term "Dv50" refers to the particle size corresponding to a cumulative volume distribution percentage of 50% for the material, which can be determined using a scanning electron microscope (SEM). Specifically, the negative electrode active material is cut using an argon ion beam, and the cross-section of the negative electrode active material is observed using a scanning electron microscope. The test sample and magnification are adjusted, and ten test images are selected at the same magnification. The particle size of all negative electrode active materials in each test image is measured, and then particle size distribution statistics are performed to obtain the volume distribution particle size Dv50 of the negative electrode active material.

[0048] In some implementations, the negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil.

[0049] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethyl methacrylate (PMMA), and carboxymethyl chitosan (CMCS).

[0050] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0051] In some embodiments, the negative electrode film layer also includes a solid electrolyte material.

[0052] In some embodiments, the solid electrolyte material may be selected from at least one of oxide solid electrolyte materials, sulfide solid electrolyte materials, halide solid electrolyte materials, nitride solid electrolyte materials, and hydride solid electrolyte materials.

[0053] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0054] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as negative electrode active material, solid electrolyte material, conductive agent, binder and any other components, in a solvent to form a negative electrode slurry. The solvent is a conventional choice in the art, and can be selected from at least one of water, ethanol, N-methylpyrrolidone (NMP), acetone, acetonitrile, toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate and butyl butyrate. The amount of solvent used is 50wt%-400wt% of the total dry mass of the prepared negative electrode slurry. The negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0055] electrolytes

[0056] The electrolyte plays a role in conducting ions between the positive and negative electrode plates.

[0057] In some embodiments, the electrochemical device includes an electrolyte, which includes a gel electrolyte, a semi-solid electrolyte, or a solid electrolyte. The solid electrolyte is formed by dispersing a solid electrolyte material with a binder (such as at least one selected from polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin) in a solvent to form a solid electrolyte slurry. The solvent is a conventional choice in the art, for example, selected from at least one selected from water, ethanol, N-methylpyrrolidone (NMP), acetone, acetonitrile, toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate, and butyl butyrate. The amount of solvent used is 50 wt% to 400 wt% of the total dry mass of the prepared solid electrolyte slurry. The solid electrolyte slurry is then coated onto a negative electrode film and / or a positive electrode film, and dried to form a solid electrolyte.

[0058] In some embodiments, the electrolyte includes a solid electrolyte material. Solid electrolyte materials have a relatively rigid structure, which can suppress the volume expansion of the negative electrode active material, thereby reducing the probability of the negative electrode active material detaching. This helps to reduce the damage to the SEI film caused by the detachment of the negative electrode active material, and thus improves the initial coulombic efficiency, capacity, and cycle performance of the electrochemical device.

[0059] In some embodiments, the solid electrolyte material includes one or more of oxide solid electrolyte materials, sulfide solid electrolyte materials, halide solid electrolyte materials, nitride solid electrolyte materials, and hydride solid electrolyte materials. Because solid electrolyte materials themselves have good mechanical ductility, the addition of the above-mentioned types of solid electrolyte materials can buffer the volume expansion of the negative electrode active material, thereby further reducing the expansion degree of the negative electrode sheet, which is more conducive to improving the initial coulombic efficiency, capacity, and cycle performance of the electrochemical device.

[0060] For example, oxide solid electrolyte materials include those with the chemical formula Li (1+x1) Q x1 M (2-x1) (PO4)3, Li (7-x2) La3Zr (2-x2) M x2 O 12 xi 3x3 Q (2 / 3-x3) MO3, Li3OCl, Li (3+x4) M y A (1-y) Q (4-z) T z One or more of the following materials. The chemical formula of which is Li (1+x1) Q x1 M (2-x1) In the (PO4)3 material, 0 ≤ x1 < 1, Q includes at least one of Al, Cr, Ba, Fe, Sc, In, Lu, Y, and La, and M includes at least one of Fe, Co, Gr, and Mn; the chemical formula is Li (7-x2) La3Zr (2-x2) M x2 O 12 In the materials, 0 ≤ x² < 1, M includes at least one of Sb, Nb, Ta, Te, and W; the chemical formula is Li. 3x3 Q (2 / 3-x3) In MO3 materials, 0.04 < x3 < 0.17, Q includes at least one of La, Sr, Ba, and Nd, and M includes at least one of Al, Ti, and Ge; the chemical formula is Li. (3+x4) M y A (1-y) Q(4-z) T z In the materials, -1 < x4 < 2, 0 ≤ y ≤ 1, 0 ≤ z ≤ 2, M includes at least one of B, Al, In, Si, Ge, Sn, Ti, W, and Mo, A includes at least one of P, As, Sb, and Bi, Q includes at least one of S and Se, and T includes at least one of F, Cl, Br, and I.

[0061] For example, sulfide solid electrolyte materials include binary compounds with the chemical formulas Li6PS5Cl, Li3PS4, Li2S-P2S5, Li2S-GeS2, and Li2S-SiS2, as well as one or more ternary compounds with the chemical formulas Li2S-MeS2-P2S5 (Me includes one or more of Si, Ge, Sn, and Al).

[0062] For example, halide solid electrolyte materials include those with the chemical formula Li x Ml a M2 b M3 c Q d X e The materials are: 1≤x≤4, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, 3≤e≤6, a+b+c=1; M1 includes one or more of B, Al, Ga, In, Sc, Y, La, Ce, Lu, Yb, Ho, Er, Tb, and Dy; M2 includes one or more of Si, Ge, Sn, Ti, Zr, and Hf; M3 includes one or more of V, Nb, and Ta; Q includes O and / or S; X includes one or more of F, Cl, Br, and I.

[0063] For example, nitride solid electrolyte materials include Li3N and Li x PO y N z One or more of the following materials. The chemical formula of which is Li x PO y N z In the material, 0 < x ≤ 1, 0 < y ≤ 1, and 0 < z ≤ 1.

[0064] For example, the hydride solid electrolyte material includes LiBH4.

[0065] Positive electrode sheet

[0066] In this application, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side surface of the positive current collector, the positive electrode film layer including a positive electrode active material.

[0067] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0068] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0069] In some embodiments, when the electrochemical device is a lithium-ion battery, the positive electrode active material may be a positive electrode active material known in the art for lithium-ion batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0070] In some embodiments, the positive electrode film layer further includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0071] In some embodiments, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0072] In some embodiments, the positive electrode film layer further includes a solid electrolyte material. As an example, the solid electrolyte material may include at least one of oxide solid electrolyte materials, sulfide solid electrolyte materials, halide solid electrolyte materials, nitride solid electrolyte materials, and hydride solid electrolyte materials.

[0073] In some embodiments, the positive electrode sheet can be prepared by dispersing the components used to prepare the positive electrode sheet, such as positive active material, solid electrolyte material, conductive agent, binder, and any other components, in a solvent to form a positive electrode slurry. The solvent is a conventional choice in the art, and may be selected from at least one of water, ethanol, N-methylpyrrolidone (NMP), acetone, acetonitrile, toluene, xylene, anisole, heptane, decane, ethyl acetate, ethyl propionate, and butyl butyrate. The amount of solvent used is 50wt%-400wt% of the total dry mass of the prepared positive electrode slurry. The positive electrode slurry is coated onto a positive current collector, and after drying, cold pressing, and other processes, the positive electrode sheet is obtained.

[0074] In some embodiments, the electrode assembly includes a wound electrode assembly. The wound structure allows for a close arrangement of electrode materials, accommodating more active material within a limited space. The positive and negative electrode sheets can be tightly wound at a uniform spacing, reducing ineffective space inside the battery and thus improving the battery's volumetric energy density.

[0075] A fundamental problem with wound electrode assemblies is that the negative electrode active material is prone to detachment at the bending points during battery use, which adversely affects the battery's lifespan. However, the electrochemical device provided in this application meets specific conditions. Achieving this condition effectively mitigates the risk of negative electrode active material detaching from the bending section of the wound electrode assembly. In this way, the electrochemical device successfully balances volumetric energy density and cycle life, improving battery energy storage capacity while ensuring stable and reliable battery operation over a longer period.

[0076] In this application, "wound electrode assembly" refers to a battery core assembly with a specific shape and performance formed by tightly winding the positive electrode sheet, the negative electrode sheet, and the electrolyte located between the positive and negative electrode sheets together in a certain manner.

[0077] In some embodiments, the electrochemical device also includes a pressurizing device for applying pressure P to the negative electrode. By including a pressurizing device, it is advantageous to precisely control the magnitude of the pressure P applied to the negative electrode.

[0078] A second aspect of this application also provides a vehicle that includes the electrochemical device provided in the first aspect. The electrochemical device can be used as a power source for the vehicle or as an energy storage unit for the vehicle. The vehicle includes, but is not limited to, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0079] Example 1

[0080] The preparation method of the electrochemical device is as follows:

[0081] (1) Preparation of negative electrode sheet

[0082] The negative electrode active material (a mixture of artificial graphite and micron-sized silicon in a mass ratio of 7:3), solid electrolyte material (Li6PS5Cl), conductive agent (a mixture of conductive carbon black and single-walled carbon nanotubes in a mass ratio of 1:0.1), and binder (a mixture of carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber in a mass ratio of 0.3:1.8:0.6) were mixed in deionized water at a weight ratio of 91.1:5:1.1:2.8 and stirred until homogeneous to obtain the negative electrode slurry; wherein, the density of the artificial graphite negative electrode active material is 2.256 g / cm³. 3 The density of micron-sized silicon is 2.33 g / cm³. 3 .

[0083] Copper foil was used as the negative electrode current collector. The negative electrode slurry was coated on both sides of the negative electrode current collector and hot-pressed at 120°C. After cutting and slitting, the negative electrode sheet was prepared with a thickness of 100μm.

[0084] The parameters of the negative electrode active material were tested using the following methods:

[0085] Volume expansion rate test:

[0086] a. The above-mentioned negative electrode active material, artificial graphite, is mixed with a conductive agent (a mixture of conductive carbon black and single-walled carbon nanotubes in a mass ratio of 1:0.1) and a binder (a mixture of carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber in a mass ratio of 0.3:1.8:0.6) in deionized water at a weight ratio of 96.1:1.1:2.8. The mixture is stirred evenly to obtain a negative electrode slurry. The negative electrode slurry is coated on both sides of the negative electrode current collector to prepare a negative electrode sheet sample containing artificial graphite.

[0087] b. The negative electrode sample prepared in step a was polished using a cross-section polisher (JEOL IB-09010CP argon ion cross-section polisher). After polishing, the cross-section of the negative electrode sample was tested using a scanning electron microscope: 20 different regions were randomly selected in the cross-section for scanning tests. At a magnification of 1000x, the particle size of all artificial graphite particles in each test region was counted, which is the particle size of artificial graphite particles in that region. The average value of the test results from multiple test regions was taken as the particle size d1 of artificial graphite particles before charging.

[0088] c. The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2, conductive agent (a mixture of conductive carbon black and single-walled carbon nanotubes in a mass ratio of 0.8:0.6), and binder (polyvinylidene fluoride) are mixed in solvent N-methylpyrrolidone at a weight ratio of 97.6:1.4:1 and stirred evenly to obtain a positive electrode slurry. Aluminum foil is used as the positive electrode current collector, and the positive electrode slurry is coated on both sides of the positive electrode current collector. After drying, cold pressing, cutting, and slitting, a positive electrode sheet is prepared.

[0089] d. Mix ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 to form an organic solvent. Dissolve LiPF6 in the organic solvent to obtain an electrolyte with a LiPF6 concentration of 1.2 mol / L.

[0090] e. Assemble the negative electrode sample containing artificial graphite prepared in step a, the positive electrode sample prepared in step c, the separator (polyethylene film), and the electrolyte prepared in step d into an electrochemical device. Charge the electrochemical device to 4.25V with a current of 0.33C. Disassemble the electrochemical device and polish the charged negative electrode sample using the method in step b. Measure the particle size d2 of the artificial graphite particles after charging. Compare the particle size of the artificial graphite particles before and after charging, according to the formula: α=(d1 / d2) 3 The calculated volume expansion rate of artificial graphite is 113%.

[0091] f. Following the test method in step ae above, replace the negative electrode active material artificial graphite with micron-sized silicon. After testing and calculation, the volume expansion rate of micron-sized silicon is found to be 300%.

[0092] Calculation of average expansion coefficient:

[0093] According to the formula: The average expansion coefficients of the two negative electrode active materials in Example 1 were calculated. It is 0.7369.

[0094] (2) Preparation of positive electrode sheet

[0095] Lithium nickel cobalt manganese oxide (LiNi) is used as the positive electrode active material. 0.8 Co 0.1 Mn 0.1 O2, solid electrolyte material Li 10 GeP2S 12 The conductive agent (a mixture of conductive carbon black and single-walled carbon nanotubes in a mass ratio of 0.8:0.6) and the binder (polyvinylidene fluoride) are mixed in the solvent N-methylpyrrolidone in a weight ratio of 92.6:5:1.4:1 and stirred evenly to obtain the positive electrode slurry.

[0096] Aluminum foil is used as the positive electrode current collector. The positive electrode slurry is coated on both sides of the positive electrode current collector. After drying, cold pressing, cutting and slitting, the positive electrode sheet is prepared with a thickness of 90μm.

[0097] (3) Preparation of electrolytes

[0098] In an argon atmosphere, solid electrolyte material Li6PS5Cl and binder (polyvinylidene fluoride) are mixed in a solvent (ethyl acetate) at a weight ratio of 95:5 and stirred until homogeneous to obtain a solid electrolyte slurry. The solid electrolyte slurry is then coated onto the negative electrode sheet prepared above and dried to form a solid electrolyte layer.

[0099] (4) Assembly of electrochemical devices

[0100] In an argon atmosphere, the negative electrode with the solid electrolyte layer is bonded to the positive electrode, so that the positive electrode is in contact with the solid electrolyte layer. After cold pressing and encapsulation, the electrode assembly is obtained by hot pressing at 50 MPa and 150°C for 10 minutes.

[0101] The electrode assembly and pressurization device were assembled into an electrochemical device. After the resulting electrochemical device was allowed to stand for 12 hours, performance tests were conducted using the following methods:

[0102] First Coulomb efficiency test:

[0103] In Example 1, the pressure P provided by the pressurizing device was 0 MPa. At 25°C and an external pressure of 0 MPa, the electrochemical device prepared in Example 1 was charged to 4.25 V using a constant current of 0.33 C, and the charging capacity D1 was recorded. After standing for 5 minutes, the electrochemical device was discharged to 2.5 V using a constant current of 0.33 C, and the discharge capacity D0 was recorded. The initial coulombic efficiency (%) of the electrochemical device was calculated as DO / D1 × 100%, and the test results are recorded in Table 1 below.

[0104] Capacity test:

[0105] In Example 1, the pressure P provided by the pressurizing device was 0 MPa. At 25°C and an external pressure of 0 MPa, the electrochemical device prepared in Example 1 was charged to 4.25V at a constant current rate of 0.33C, then charged to 0.05C at a constant voltage rate. After standing for 5 minutes, it was discharged to 2.5V at a constant current rate of 0.33C. The discharge capacity at this point was recorded, which is the 0.33C discharge capacity. The test results are recorded in Table 1 below.

[0106] Cyclic performance test:

[0107] In Example 1, the pressure P provided by the pressurizing device was 0 MPa. At 25°C and an external pressure of 0 MPa, the electrochemical device prepared in Example 1 was charged at a constant current of 0.33C to 4.25V, then charged at a constant voltage of 4.25V to 0.05C, and discharged at 0.33C to 2.5V, constituting the first cycle. The discharge capacity of the first cycle is denoted as C0. This process is repeated 100 times, and the discharge capacity of the 100th cycle is denoted as Cn. The capacity retention rate after 100 cycles is calculated as (Cn / CO) × 100%.

[0108] Example 2

[0109] The electrochemical device was prepared using the same method as in Example 1, except that the pressure P provided by the pressurizing device was adjusted from 0 MPa to 20 MPa during the performance testing of the electrochemical device.

[0110] Example 3

[0111] The electrochemical device was prepared using the same method as in Example 1, except that the pressure P provided by the pressurizing device was adjusted from 0 MPa to 50 MPa during the performance testing of the electrochemical device.

[0112] Example 4

[0113] The electrochemical device was prepared using the same method as in Example 1, except that the pressure P provided by the pressurizing device was adjusted from 0 MPa to 200 MPa during the performance testing of the electrochemical device.

[0114] Example 5

[0115] The electrochemical device was prepared using the same method as in Example 1, except that the pressure P provided by the pressurizing device was adjusted from 0 MPa to 300 MPa during the performance testing of the electrochemical device.

[0116] Example 6

[0117] The electrochemical device was prepared using the same method as in Example 2, except that in the preparation of the negative electrode, the negative electrode active materials artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 were replaced with artificial graphite and micron-sized silicon (mass ratio of 1:1).

[0118] Example 7

[0119] The electrochemical device was prepared using the same method as in Example 2, except that, in the preparation of the negative electrode, the silicon-based material micron-silicon in the negative electrode active material was replaced with nano-silicon.

[0120] Example 8

[0121] The electrochemical device was prepared using the same method as in Example 2, except that in the preparation of the negative electrode, the silicon-based material micron-silicon in the negative electrode active material was replaced with silicon suboxide.

[0122] Example 9

[0123] The electrochemical device was prepared using the same method as in Example 2, except that the silicon-based material micron-silicon in the negative electrode active material was replaced with a silicon-carbon composite during the preparation of the negative electrode.

[0124] Example 10

[0125] The electrochemical device was prepared using the same method as in Example 2, except that in the preparation of the negative electrode, the carbon-based material artificial graphite in the negative electrode active material was replaced with natural graphite.

[0126] Example 11

[0127] The electrochemical device was prepared using the same method as in Example 2, except that the carbon-based material artificial graphite in the negative electrode active material was replaced with mesophase carbon microspheres during the preparation of the negative electrode sheet.

[0128] Example 12

[0129] The electrochemical device was prepared using the same method as in Example 2, except that in the preparation of the negative electrode, the carbon-based material artificial graphite in the negative electrode active material was replaced with soft carbon.

[0130] Example 13

[0131] The electrochemical device was prepared using the same method as in Example 2, except that, in the preparation of the negative electrode, the carbon-based material artificial graphite in the negative electrode active material was replaced with hard carbon.

[0132] Example 14

[0133] The electrochemical device was prepared using the same method as in Example 4, except that in the preparation of the negative electrode, the negative electrode active materials artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 were replaced with artificial graphite.

[0134] Example 15

[0135] The electrochemical device was prepared using the same method as in Example 4, except that the negative electrode active materials artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 were replaced with micron-sized silicon during the preparation of the negative electrode sheet.

[0136] Example 16

[0137] The electrochemical device was prepared using the same method as in Example 4, except that in the preparation of the negative electrode, the artificial graphite and micron-sized silicon (mass ratio of 7:3) used in Example 1 were replaced with lithium titanate.

[0138] Comparative Example 1

[0139] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, the negative electrode active materials artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 were replaced with artificial graphite and micron-sized silicon (mass ratio of 1:1).

[0140] Comparative Example 2

[0141] The electrochemical device was prepared using the same method as in Example 1, except that the negative electrode active materials, artificial graphite and micron-sized silicon (mass ratio of 7:3), were replaced with micron-sized silicon during the preparation of the negative electrode.

[0142] Comparative Example 3

[0143] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, the negative electrode active material artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 was replaced with micron-sized silicon, and the pressure P provided by the pressurizing device was adjusted from 0 MPa to 100 MPa.

[0144] Comparative Example 4

[0145] The electrochemical device was prepared using the same method as in Example 1, except that in the preparation of the negative electrode, the negative electrode active materials artificial graphite and micron-sized silicon (mass ratio of 7:3) in Example 1 were replaced with artificial graphite and micron-sized silicon (mass ratio of 3:7), and the pressure P provided by the pressurizing device was adjusted from 0 MPa to 20 MPa.

[0146] The negative electrode active materials in Examples 1 to 16 and Comparative Examples 1 to 4 were tested using the same test methods as in Example 1, and the performance of the electrochemical devices was tested. The test results are shown in Table 1 below.

[0147] Table 1

[0148]

[0149]

[0150] As can be seen from the data in Table 1, compared with Comparative Examples 1 to 4, the average expansion coefficient of the n negative electrode active materials in the battery devices prepared in Examples 1 to 16 is... The pressure P of the environment where the negative electrode is located satisfies the following relationship: This results in the electrochemical devices of Examples 1 to 16 having improved capacity, initial coulombic efficiency, and cycle performance.

[0151] Example 17

[0152] The electrochemical device was prepared using the same method as in Example 2, except that the solid electrolyte material Li6PS5Cl was replaced with Li3PS4 during the preparation of the electrolyte.

[0153] Example 18

[0154] The electrochemical device was prepared using the same method as in Example 2, except that the solid electrolyte material Li6PS5Cl was replaced with Li during the electrolyte preparation process. 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0155] Example 19

[0156] The electrochemical device was prepared using the same method as in Example 2, except that the solid electrolyte material Li6PS5Cl was replaced with Li3N during the preparation of the electrolyte.

[0157] Example 20

[0158] The electrochemical device was prepared using the same method as in Example 2, except that the solid electrolyte material Li6PS5Cl was replaced with LiBH4 during the preparation of the electrolyte.

[0159] Example 21

[0160] The electrochemical device was prepared using the same method as in Example 2, except that the solid electrolyte material Li6PS5Cl was replaced with Li3InCl6 during the preparation of the electrolyte.

[0161] The negative electrode active materials in Examples 17 to 21 were tested using the same test methods as in Example 1, and the electrochemical devices were tested for performance. The test results are shown in Table 2 below. For ease of comparison, the test results of Example 2 are also shown.

[0162] Table 2

[0163]

[0164]

[0165] As can be seen from the data in Table 2, the electrochemical devices obtained by adding the above-mentioned types of solid electrolyte materials in Examples 2 and 17 to 21 have improved capacity, first coulombic efficiency and cycle performance.

[0166] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. An electrochemical device, characterized in that, The electrochemical device includes an electrode assembly; The electrode assembly includes a negative electrode sheet, wherein the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer includes a set of negative electrode active materials, the set of negative electrode active materials includes n kinds of negative electrode active materials, n≥1; The average expansion coefficient of the n types of negative electrode active materials The pressure P of the environment where the negative electrode is located satisfies: in, x i The mass fraction of the i-th negative electrode active material among the n types of negative electrode active materials, based on the mass of the set of negative electrode active materials; α i ρ is the volume expansion rate of the i-th negative electrode active material; i denoted as the density of the i-th type of negative electrode active material.

2. The electrochemical device according to claim 1, characterized in that, The pressure P is 0MPa-300MPa.

3. The electrochemical device according to claim 1 or 2, characterized in that, The negative electrode active material includes carbon-based materials, silicon-based materials, or lithium titanate.

4. The electrochemical device according to claim 3, characterized in that, The set of negative electrode active materials includes the carbon-based material and the silicon-based material, or the set of negative electrode active materials includes the lithium titanate.

5. The electrochemical device according to claim 3 or 4, characterized in that, The carbon-based materials include one or more of the following: artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon, and hard carbon.

6. The electrochemical device according to any one of claims 3 to 5, characterized in that, The silicon-based material includes one or more of elemental silicon, silicon oxides, and silicon-carbon composites.

7. The electrochemical device according to any one of claims 1 to 6, characterized in that, The electrolyte includes solid electrolyte materials.

8. The electrochemical device according to claim 7, characterized in that, The solid electrolyte material includes one or more of the following: oxide solid electrolyte material, sulfide solid electrolyte material, halide solid electrolyte material, nitride solid electrolyte material, and hydride solid electrolyte material.

9. The electrochemical device according to any one of claims 1 to 8, characterized in that, The positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector. The positive electrode film layer includes a positive electrode active material, which includes at least one of a lithium phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds.

10. The electrochemical device according to any one of claims 1 to 9, characterized in that, The electrode assembly includes a wound electrode assembly.

11. The electrochemical device according to any one of claims 1 to 10, characterized in that, The electrochemical device further includes a pressurizing device for providing the pressure P to the negative electrode plate.

12. A vehicle, characterized in that, The vehicle includes the electrochemical device according to any one of claims 1 to 11.